PENGARUH PARTISIPASI DALAM PENGELOLAAN HUTAN KEMASYARAKATAN TERHADAP KESEJAHTERAAN PETANI (STUDI KASUS GAPOKTAN MANDIRI LESTARI KPH VIII BATU TEGI) - Ezra Zeilika; Hari Kaskoyo; Christine Wulandari (Lambung Mangkurat University-Indonesia, 2021)
Community forestry in the management area of BatuTegi is a form of program forest management that involves the community in the rehabilitation of protected forests. The Community forestry scheme in this region has been implemented by synergizing the ecological, economy and social functions with the aim of ensuring sustainable forest preservation. To achieve these objectives, farmers need to participate in management. This study aims to determine the effect of farmer participation on the welfare of farmer case studies in the Mandiri Lestari forest farmers community. The research method used quantitative descriptive with samples taken in December 2019-February 2020 in a proportional random sampling of 37 respondents and data analyzed using quantitative statistical Structural Equation Modeling (SEM) techniques through the Partial Least Square (PLS) approach. The analysis shows that participation in planning had the greatest influence on economic welfare with a value of 1,672, participation in the utilization of results has a second impact with a value of 1,358, and participation in implementation is the least influential variable on economic welfare. Whereas for social welfare the participation variable in implementation had the greatest influence with a value of 1,054, the participation variable in the utilization of results has a second impact with a value of 1,021 and the participation variable in planning is the variable that had the least effect on the welfare of farmers